The Effect of Zataria multiflora on Th1/Th2 and Th17/T Regulatory in a Mouse Model of Allergic Asthma - Kianmehr, Majid; Haghmorad, Dariush; Nosratabadi, Reza; Rezaei, Abdolrahim; Alavinezhad, Azam; Boskabady, Mohammad Hossein (Frontiers in Pharmacology, 2017)
Asthma is a chronic inflammatory disease with no definite treatment and more research is needed to overcome this condition. The aim of this study was to investigate the effect of the extract of Zataria multiflora (Z. multiflora) as a medicinal plant on cytokine genes expression in an experimental mouse model of asthma. Adult mice were randomly divided into the following groups: control (C), untreated asthma (A), asthmatic groups treated with dexamethasone (D) and Z. multiflora extract (200,400 and 800 µg/mL) (Z1, Z2, and Z3, respectively), (for groups C, A and D n=5 and for groups Z1, Z2 and Z3 n=6). For induction of the mouse model of asthma, animals were sensitized with intraperitoneal injection and inhalation of ovalbumin (OVA). The number of T helper (Th) subtype cells (using flow cytometry) and the levels of IFN-γ, FOXP3, IL-4, TGF-β, IL-17 gene expression (by real time PCR) were assessed in mice splenocytes. The observed changes in spleen cells of group A compared to group C were increased number of Th2 and Th17 cells, enhancement of gene expression of IL-4, IL-17 and TGF-β (p<0.001 for all cases), reduction of Th1 cells and Th1/Th2 ratio (p<0.001 for both cases) and decrease in gene expression of IFN-γ, FOXP3 and IFN-γ/IL-4 ratio (p<0.01 for IFN-γ and p<0.001 for other cases). The observed changes in spleen cells of treated compared to untreated A group were enhancement of Treg cells and Th1/Th2 ratio (p<0.001 for both cases), increase in IFN-γ (p<0.05) and FOXP3 (p<0.001) gene expression and IFN-γ/IL-4 ratio (p<0.01) as well as reduction of Th2 and Th17 cells (p<0.01 to p<0.001), decrease gene expression of IL-4, IL-17 and TGF-β (p<0.05 to p<0.001). The findings showed that the extract of Z. multiflora decreased pro-inflammatory cytokines in asthma (IL-4 and IL-17 and TGF-β) but increased anti-inflammatory cytokines (IFN-γ) gene expression and the number of Treg (FOXP3) in splenocytes of asthmatic mice which may indicate the specific therapeutic effect of the plant extract in allergy, autoimmunity and infectious diseases via potentiating Th1 and suppressing Th2 and Th17 cells.